Tradisi Suran Masyarakat Traji: Sebuah Kajian Antropologi Linguistik - Nur Alfi Mu’anayah (Jurnal Ilmiah Citra Ilmu : Kajian Kebudayaan dan Keislaman, 2016)
This research discusses Suran tradition by Traji society in Temanggung, Central Java. It aims at finding linguistic units, determining their meaning, and identifying cultural background that influences the tradition. Data in this research are linguistic units found on Suran. The analysis showed that names of serving are Traji’s cultural symbols, and the Javanese song lyric describes their culture. Then, there are two cultural systems that influence the tradition intensively, they are agriculture and religion & belief.